Groundwater treatment by combining the electrokinetic process with permeable reactive barriers containing granular activated carbon - M. Rokneddin; N. Mokhtarani (مهندسی عمران شریف, 2025)
Today, groundwater plays an undeniable role in supplying water for the communities. In recent years, the extensive use of chemical fertilizers and improper wastewater treatment from industrial sites has led to several environmental problems, such as an increase in the concentration of nitrate and sulfate in underground and surface water. Nitrate and sulfate in water sources cannot be easily separated due to their high solubility, so their separation methods are costly. Although permeable reactive barriers are one of the new methods used for on-site treatment of water sources, the early saturation of the substrate used is one of its disadvantages. One of the methods used to solve this problem is the electrokinetic process. The purpose of this research, which was conducted on a laboratory scale, was to combine the electrokinetic process and permeable reactive barriers containing modified activated carbon to simultaneously remove nitrate and sulfate from contaminated water. This research used a glass reactor with dimensions of 15*30*100 , and the space inside was divided into several sections using a nylon filter. Also, a layer of sand was placed on the reactive substrate, and two graphite electrodes were placed on top of the soil layer and under the reactive substrate to create an electric current and ensure migration conditions. The effect of , nitrate, and sulfate initial concentration, activated carbon to sand ratio, and the electrical gradient on the performance of the process was investigated, and the optimal conditions for improving the system efficiency were determined using the classical method. Based on the results of experiments, using an electrical gradient of 1.5 in optimal conditions (initial nitrate concentration 200 , initial sulfate concentration 450 , inlet flow rate 3.3 , and the ratio of active carbon to sand 1:2) the adsorption capacity increased by 83% for nitrate and 86% for sulfate. In addition, under these conditions and by controlling the concentration of nitrate and sulfate within standard permissible limits, the period of operation of the system for nitrate increased from 40 hours to 100 hours and for sulfate from 45 hours to 110 hours. According to the results, the integrated process is a reliable method for the simultaneous removal of sulfate and nitrate from groundwater.